(untitled) (Revista Electrónica Calidad en la Educación Superior, 2018)
The Information and Communication Technologies (ICT) imply changes not only globally in society, but also in the education systems. Professors must acquire the necessary skills that enable them to integrate ICT in different educational scenarios. Parallel to the proposal of a curricular redesign of the course Didactic Resources for English Teaching, it was presented the design and production of a multimedia to inform and provide teachers, who teach the course, on technological tools applicable to English teaching and learning. As a systematization of the experience, this article presents a model as a guide for the various elements that explicitly make up the phases of design and production of a multimedia material. Likewise, evaluative aspects are included after the multimedia design and production process, which helped to improve the quality of the material from a perspective of technical, aesthetic and content aspects. Key Words: ICT; multimedia; design; production.